Undesirables : a Holocaust journey to North Africa - Boum, Aomar 1970- (Stanford studies in Jewish history and culture, 2023)
"In this gripping graphic novel, a Jewish journalist encounters an extension of the horrors of the Holocaust in North Africa. In the lead-up to World War II, the rising tide of fascism and antisemitism in Europe foreshadowed Hitler's genocidal campaign against Jews. But the horrors of the Holocaust were not limited to the concentration camps of Europe: antisemitic terror spread through Vichy French imperial channels to France's colonies in North Africa, where in the forced labor camps of Algeria and Morocco, Jews and other "undesirables" faced brutal conditions and struggled to survive in an unforgiving landscape quite unlike Europe. In this richly historical graphic novel, historian Aomar Boum and illustrator Nadjib Berber take us inside this lesser-known side of the traumas wrought by the Holocaust by following one man's journey as a Holocaust refugee.